Humor negro en el contexto de la muerte encefálica - Baranowski, Carolina Andrea; Martínez, Bárbara (Pontificia Universidad Católica del Perú, 2024)
In this article, we propose to analyze how healthcare personnel involved in organ and tissue procurement activities use black humor during their daily work. The objective here is twofold: on the one hand, following previous studies, we are interested in showing the role of black humor as a way of dealing with death. On the other hand, we suggest that, in a parallel and complementary way, in this context black humor exposes a performative sense as a form of agency that attempts to modify an adverse reality. This work combines the methodological tools provided by ethnography and conducting open, multi-session interviews. The events revealed during the fieldwork and interviews that associate humor and brain death show the uses, limits and ways in which black humor operates in daily healthcare work of physical and emotional complexity.

En este artículo nos proponemos analizar cómo el personal de salud vinculado a la actividad de procuración de órganos y tejidos utiliza el humor negro durante su labor cotidiana. Aquí el objetivo es doble: por un lado, siguiendo estudios anteriores, nos interesa mostrar el rol del humor negro como modo de lidiar con la muerte. Por otro lado, sugerimos que, de forma paralela y complementaria, el humor negro en este contexto expone un sentido performático como forma de agencia que intenta modificar una realidad adversa. Este trabajo combina las herramientas metodológicas brindadas por la etnografía y la realización de entrevistas abiertas de sesiones múltiples. Los acontecimientos relevados durante el trabajo de campo y las entrevistas que asocian el humor y la muerte encefálica evidencian los usos, límites y modos en los que el humor negro opera en la labor cotidiana sanitaria de complejidad física y emocional.
Dark Humor in the Context of Brain Death
Keywords: Black humor; Brain death; Health personnel; Performance; Ethnography; Humor negro; Muerte encefálica; Personal de salud; Performance; Etnografía; https://purl.org/pe-repo/ocde/ford#5.04.03